In vitro 3-D culture demonstrates incompetence in improving maintenance ability of primary hepatocytes - Ullah, Imran; Kim, Yeongji; Lim, Malgum; Oh, Keon Bong; Hwang, Seongsoo; Shin, Yurianna; Kim, Youngim; Im, Gi-Sun; Hur, Tai-Young; Ock, Sun A (Animal cells and systems, 2017)
Primary hepatocytes (PHs) are considered the 'gold standard' in drug screening owing to their ability to express many drug-metabolizing enzymes and transporters. Culturing hepatocytes and maintaining their fate in vitro is a major issue since last decade. The main problem with in vitro hepatocytes culture is that they rapidly lose their hepatic morphology and liver-specific functions in culture. Herein, we isolated rat PHs, and cultured them in monolayers (2-D) and spheroids (3-D). The 2-D-cultured PHs exhibited elongated morphology, whereas the 3-D-cultured PHs exhibited spheroid morphology with gradual diameter decrease until 7 days. After 7 days of in vitro culture, PHs were analyzed for the expression of hepatic (Alb, Tf, and Afp) and apoptotic markers (Bax and Bcl2), and co-expression of CYP3A1 and Abumin after 2 and 7 days. Furthermore, in both cultures, PHs were induced with 3-methylcholanthrene (3-MC, Cyp1a-specific inducer) and dexamethasone (Cyp3a-specific inducer) for 48 and 72 h, respectively. The mRNA levels of Cyp1a and Cyp3a were analyzed in induced (3-MC, dexamethasone) and non-induced PHs. After 7 days of in vitro culture, PHs exhibited dramatic downregulation of hepatic marker expression in both cultures. Furthermore, apoptotic marker expression was higher in the 2-D-cultured PHs than 3-D-cultured PHs. The mRNA levels of Cyp1a and Cyp3a indicated higher RNA content in the 2-D-cultured PHs after 48 h of induction. Therefore, we concluded that there was no significant difference between the culture systems, and further studies are required to identify the essential components for in vitro PH culture rather than culture systems.